Electronic Energy Levels and Intra-Band Transitions in the Conduction Band of a Zn1-xMgxO /ZnO/Zn1-xMgxO Quantum Well Heterostructures - Moustapha Thiam; Aminata Diaw; Amaky Badiane; Omar Absatou Niasse; Amadou Diao; Moulaye Diagne; Bassirou Lo; Bassirou Ba (Current Research Progress in Physical Science Vol. 3, 2024)
In the last few years, semiconductor-based quantum well structures have been intensively investigated because of their interesting optical and electrical properties. This paper studies a quantum well heterostructure made up of a zinc oxide (ZnO) thin layer (well) sandwiched between two Zn1-xMgxO layers acting as potential barriers. The material is chemically and thermally stable, non-toxic and abundant in nature. Setting the width of the well to a = 10 nm, the allowed quantum states in the conduction band (CB) and the wave function profiles are examined for two values of magnesium concentration: x = 0.1 and x = 0.2. The calculated wavelengths corresponding to intra-band transitions in the conduction band are in the infrared domain of the electromagnetic spectrum. These wavelengths depend on x, allowing to control the optoelectronic properties of the quantum well by adjusting the concentration x during the growth process. This suggests that it is possible to control the optoelectronic properties of a quantum well by adjusting the concentration during the growth process, in order to obtain the desired wavelength for a semiconductor laser.